Implementación contable en la empresa comercial molinos Jaramillo de la ciudad de Loja, periodo del 01 de octubre al 31 de diciembre de 2021 - Rivera Vega, Andrea Anabell (2022)
The thesis project entitled The Accounting implementation in the “Molinos Jaramillo” commercial company in Loja city, period from October 1st to December 31st, 2021 was developed taking into account the company’s needs through an accounting implementation where all the activities carried out by it are integrated, it will allow to know the economic-financial situation, take relevant decisions and find out errors arise during the process, therefore improving the operation of the company and achieving the objectives proposed by it. In order to accomplish with the objectives proposed in the thesis project, the stocktaking was carried out through the physical verification of all the properties, rights and obligations of the company, followed by the Initial Situation Statement. Subsequently, the Chart of Accounts was structured according to the company’s needs, which was used to develop the Book Accounts containing the description movement and balance of each of them, then the source documentation was arranged properly to design the auxiliary records where the sales and purchase bills were detailed, facilitating the control of the operations carried out, once these results were obtained, the values in the daily journal were entered in order to transfer the values to the General book and obtain the balances of each account, allowing the preparation of the Trial Balance, followed by the respective adjustments until the financial statements were obtained, such as Income Statement, Statement of Financial Position and Statement of Cash Flows. Finally, it was concluded with the descriptions of the conclusions and the recommendations that were considered appropriate for the implementation of accounting in the commercial company "Molinos Jaramillo", mentioning that the importance of this process benefits in a positive way the economic development of the business, so that by obtaining economic-financial information it is a source of support for the owner to keep an adequate record, control and consolidation of the operations carried out, and therefore for good decision making